Mathematics Learning Problem Based Learning Model in Improving Students' Mathematical Representation Ability: A Meta-Analysis - Rahmy, Aghnesia; Sutiarso, Sugeng (Universitas Teknokrat Indonesia, 2025)
This research aims to examine the effect size of studies that discuss the application of the Problem Based Learning model as an effort to improve students' mathematical representation skills. The statistical procedures used in this study were based on the meta-analysis procedures namely: (a) calculating the effect size of each primary study; (b) conducting heterogeneity tests and selecting estimation models; (c) check for publication bias; (d) calculate the p-value to test the research hypothesis. The primary studies used were 10 studies obtained from the Google Scholar search engine with publication years between 2018 and 2024. The results of statistical calculations showed that the overall effect size of the studies used was 0.600, which is included in the moderate effect size category with a standard deviation of 0.171. This finding means that the application of the Problem Based Learning model in mathematics learning has a moderate influence on students' mathematical representation skills.